Barriers to Quality Perioperative Care Delivery in Low- and Middle-Income Countries: A Qualitative Rapid Appraisal Study. (24th August 2022) - Bedwell, Gillian J.; Dias, Priyanthi; Hahnle, Lina; Anaeli, Amani; Baker, Tim; Beane, Abi; Biccard, Bruce M.; Bulamba, Fred; Delgado-Ramirez, Martha B.; Dullewe, Nilmini P.; Echeverri-Mallarino, Veronica; Haniffa, Rashan; et al.
Abstract : BACKGROUND: Provision of timely, safe, and affordable surgical care is an essential component of any high-quality health system. Increasingly, it is recognized that poor quality of care in the perioperative period (before, during, and after surgery) may contribute to significant excess mortality and morbidity. Therefore, improving access to surgical procedures alone will not address the disparities in surgical outcomes globally until the quality of perioperative care is addressed. We aimed to identify key barriers to quality perioperative care delivery for 3 "Bellwether" procedures (cesarean delivery, emergency laparotomy, and long-bone fracture fixation) in 5 low- and middle-income countries (LMICs). METHODS: Ten hospitals representing secondary and tertiary facilities from 5 LMICs were purposefully selected: 2 upper-middle income (Colombia and South Africa); 2 lower-middle income (Sri Lanka and Tanzania); and 1 lower income (Uganda). We used a rapid appraisal design (pathway mapping, ethnography, and interviews) to map out and explore the complexities of the perioperative pathway and care delivery for the Bellwether procedures. The framework approach was used for data analysis, with triangulation across different data sources to identify barriers in the country and pattern matching to identify common barriers across the 5 LMICs. RESULTS: We developed 25 pathway maps, undertook >30 periods of observation, and held >40 interviews with patients and clinical staff. Although the extent and impact of the barriers varied across the LMIC settings, 4 key common barriers to safe and effective perioperative care were identified: (1) the fragmented nature of the care pathways, (2) the limited human and structural resources available for the provision of care, (3) the direct and indirect costs of care for patients (even in health systems for which care is ostensibly free of charge), and (4) patients' low expectations of care. CONCLUSIONS: We identified key barriers to effective perioperative care in LMICs. Addressing these barriers is important if LMIC health systems are to provide safe, timely, and affordable provision of the Bellwether procedures.